Analisis Pasca Kolonialisme: Mendobrak Standar Kecantikan “Kulit Putih” dan Peluang Pastoral Gereja Indonesia Menjadi Agen Perubahan Sosial - Xalastinus Jasper Hanta; Agustinus Abraham (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2026)
This study analyzes the construction of the “white skin” beauty standard in Indonesia through a postcolonial perspective and examines the pastoral opportunities of the Catholic Church as a driving force in the discourse. This beauty standard is understood as a form of symbolic domination rooted in the legacy of colonialism, issues of race and gender, and socio-economic-capitalistic interests that are reproduced through the media and the cosmetics industry. The research uses a literature study method utilizing books and scientific journals. This method is enriched with structured interviews with young Catholics to explore critical awareness and the potential for transformative action. The interview process began with the preparation of questions, the search for respondents, the interviews themselves, and the recording of the interview results. The results of this study indicate that a single beauty narrative causes discrimination, feelings of inferiority, and lack of self-confidence in dark-skinned women, so that discursive criticism of the hegemony of colonial beauty standards is very necessary through critical education, strengthening local cultural identities, and developing diverse beauty standards. In this context, the Catholic Church, through its theology of inculturation and pastoral accompaniment, has a strategic role to play in promoting respect for diversity, human dignity, and social justice. Thus, the Church can function as a prophetic agent that dismantles the hegemony of colonial beauty standards and affirms the pluralistic and dignified identity of Indonesian women.